The Translation of the Critique of Pure Reason into Italian: Erscheinungen, Grenzen, Schranken and other discoveries: - Sánchez Rodríguez, Costantino (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The essay takes as its starting point a new translation of the Critique of Pure Reason into Italian, which turned out to be a real cognitive discovery. Knowledge of a text is not only a presupposition, but also paradoxically a peculiar effect of the translation itself. In Kant's case, translation comes to be a mode not only incidental, but in some cases almost necessary for understanding the author's writing. Indeed, in the latter, something specific happens at the grammatical and syntactical level that determines in its concrete making the semantics of transcendental thought. It is Kant himself who is the first translator-interpreter of the archive of concepts of the metaphysical-transcendental tradition, which with him is curved into a new critical-transcendental translation. The essay proposes two case studies of this translation work done first by Kant himself and then of course by his contemporary translator. The first case concerns the term Erscheinung/Phänomen, the second the terms Grenze/Schranke. In both, the translation leads from within the text to a questioning of the usual interpretations of these topoi.